Investigation of renal osteodystrophy among hemodialysis patients referring to Towhid Hospital, Sanandaj, Iran - Sedighi-Gourabi, Vahid; Afkhamzadeh, Abdorrahim; Nikkhu, Bahram; Rahimi-Rastgoo, Babak; Habibi, Savgand; Moradinia, Gholam (Chronic Diseases Journal, 2014)
BACKGROUND: Renal osteodystrophy is a major complication among dialysis patients that can lead to muscle weakness, and bone pain and fractures by minor trauma. In the present study, the frequency of these symptoms and status of blood markers among dialysis patients are discussed. METHODS: In a crass-sectional study, blood sample was obtained from 82 hemodialysis patients for calcium (Ca), phosphorus (P), alkaline phosphatase (ALP), and parathyroid hormone (PTH) level measurement. Radiography of the right hand was performed for 57 patients. Data analysis was performed via SPSS by using chi-square test, Fisher’s exact test, and Pearson correlation coefficient. RESULTS: The prevalence of osteodystrophy among dialysis patients was 72% (59 patients), including 29 patients with high bone turnover and 30 patients with adynamic bone disease. Moreover, 24 patients (29.3%) were hypocalcaemic and 25 patients (30.5%) were hypercalcemic. In addition, 25 (30.5%) patients had hyperphosphatemia. In the present study, 82 patients, 40 male (48.8%) and 42 female (51.2%), were recruited. Patients’ mean age ± standard deviation was 55.77 ± 14.99. There was a relation between increase in age and adynamic bone disease (P = 0.004). Calcium level had a significant association with radiologic manifestation of renal osteodystrophy (P = 0.007). PTH levels had moderate correlation with ALP level (r = 0.55). CONCLUSION: In the present study, there was a relation between age and adynamic bone disease; meaning that by increasing of age, the prevalence of adynamic bone disease also increased. There was a strong positive correlation between PTH and ALP.